Acute nontraumatic subdural intracranial hematoma: rare complication of percutaneous vertebroplasty - Halikulov, Elbek S.; Jumanov, Kamaliddin N.; Juraev, Eduard S. (Ukrainian Neurosurgical Journal, 2017)
The paper describes a rare case of acute intracranial subdural hematoma in a 22-year old woman followed by fluoroscopy-guided percutaneous vertebroplasty for vertebral hemangioma. Percutaneous vertebroplasty was performed in usual manner on prone position. The next day a female patient complained of headache, nausea and vomiting. MRI images revealed subdural hematoma compressing the brain. Intracranial vascular abnormalities and coagulopathies associated with subdural intracranial hematoma were not evident on CT-angiography and in laboratory tests. Craniotomy was performed to remove the subdural hematoma, and the patient fully recovered. Percutaneous vertebroplasty was emphasized to be followed by rare intracranial complications, awareness of which is very important for the surgeon for complications prevention and treatment outcomes improvement.